A Deep Learning Based Method for Detecting of Wear on the Current Collector Strips' Surfaces of the Pantograph in Railways - Karaduman, Gulsah; Akin, Erhan (Ieee-Inst Electrical Electronics Engineers Inc, 2020)
In pantographs, current collector strips transmit the electrical energy they receive from the catenary to the locomotive and provide the necessary power for the locomotive's movement. In order for the current collector strips to transmit electricity to the locomotive in a healthy way, their surface must be smooth. Wear on the surface of the current collector strips reduces conductivity and can create arcs, endangering the health and safety of the pantograph and catenary system. In this paper, a Convolutional Neural Network (CNN) architecture is developed to detect wear on the current collector strips. Images obtained from pantographs used on railways were created with a clean and improved data set using Hough Transform and Power Law Transform. The created dataset contains 909 pantograph images. This dataset was trained and tested with both the developed CNN architecture and classic deep learning architectures (ResNet50, VGG16). The experimental results show that the developed CNN architecture's training results and test results are more successful than classical architectures.
Keywords: Strips; Machine learning; Rail transportation; Wires; Transforms; Image processing; Sensor systems; Convolutional neural network; hough transform; power law transform; ResNet50; VGG16